2014
DOI: 10.1093/pcp/pcu127
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylglucosamine-1-P Uridylyltransferase 1 and 2 Are Required for Gametogenesis and Embryo Development in Arabidopsis thaliana

Abstract: Although N-acetylglucosamine-1-P uridylyltransferase (GlcNAc1pUT) that catalyzes the final step of the hexosamine biosynthetic pathway and is conserved among, organisms, produces UDP-N-acetylglucosamine (UDP-GlcNAc), an essential sugar moiety involved in protein glycosylation and structural polymers, its biological function in plants remains unknown. In this study, two GlcNA.UT genes were characterized in Arabidopsis thaliana. The single mutants glcna.ut1 and glcna.ut2 revealed no obvious phenotype, but their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…In plants, defects in the enzymes involved in de novo UDP‐GlcNAc synthesis severely impact growth and development[11,16,17]. We demonstrated the significant function of AtGNK for UDP‐GlcNAc synthesis; however, we did not observe morphological changes or growth defects in the atgnk mutant compared with the wild type, which was most likely because of a sufficient supply of UDP‐GlcNAc from the de novo synthesis pathway under our growth conditions.…”
Section: Discussionmentioning
confidence: 59%
“…In plants, defects in the enzymes involved in de novo UDP‐GlcNAc synthesis severely impact growth and development[11,16,17]. We demonstrated the significant function of AtGNK for UDP‐GlcNAc synthesis; however, we did not observe morphological changes or growth defects in the atgnk mutant compared with the wild type, which was most likely because of a sufficient supply of UDP‐GlcNAc from the de novo synthesis pathway under our growth conditions.…”
Section: Discussionmentioning
confidence: 59%
“…The reproductive abilities of transgenic plants were also compromised in studies of mutants of some other enzymes involved in nucleotide sugar synthesis, e.g. UDP-N-acetylglucosamine pyrophosphorylase (Chen et al, 2014) and CMP-3-deoxy-D-manno-octulosonic acid synthetase (Kobayashi et al, 2011). Whereas all these studies underlined the importance of nucleotide sugars for plant reproduction, other more refined approaches are needed to define physiological roles of the UDP-sugar producing pyrophosphorylases.…”
Section: Discussionmentioning
confidence: 99%
“…Since the impact of NO on plant metabolism is related to its concentration being precisely regulated by the plant, depending on its abundance NO may provoke opposite effects under physiological and stress conditions [ 23 , 50 ]. In this study we reported how potato leaves from the same genotypes challenged with pathogens of different lifestyles, e.g.…”
Section: Discussionmentioning
confidence: 99%